ROLES, RESPONSIBILITIES AND FUNCTIONS OF PHARMACY TECHNICIANS. A SCOPING REVIEW - Najd Awwadh Al Otaibi, Jabbar Faleh Jabbar Alkhathami, Majed Nasser Alghamdi, Nojoud Mohammed Mujammami, Yasir Ahmed Mohammed Alzahrani (Chelonian Research Foundation, 2024)
Pharmacy technicians play a crucial role in the healthcare system, supporting pharmacists in the preparation, dispensing, and management of medications. With a diverse range of tasks and responsibilities, they contribute to the efficiency of pharmacy operations and the safe delivery of pharmaceutical care. This article aims to explore the roles, responsibilities, and functions of pharmacy technicians, examining their scope of practice, the skills required, and their impact on patient care. Through a detailed review of their duties, the article highlights the evolving nature of the pharmacy technician's role in both community and hospital settings, with emphasis on regulatory considerations, professional standards, and emerging trends in the profession.